2004
DOI: 10.1002/bit.20122
|View full text |Cite
|
Sign up to set email alerts
|

Chromatofocusing of peptides and proteins using linear pH gradients formed on strong ion‐exchange adsorbents

Abstract: Although it is commonly believed that a column packing used for chromatofocusing must have an ''even'' buffering capacity in order to produce a linear pH gradient, it is demonstrated here that linear pH gradients suitable for chromatofocusing can be produced on a column packing having a minimal buffering capacity. In particular, if either a strong-acid cation-exchange column packing or a strongbase anion-exchange column packing is presaturated with either a weak acid titrated with a strong base, or a weak base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Due to technically limited resolution of the pH-gradient [28], a wide peak base was observed. Kang and Frey [37] compared different column packing of strong and weak ion-exchange adsorbents for chromatofocusing with regard to the linearity of the pH-gradient and resolution. It was reported that strong ion-exchange adsorbents could achieve the same or even slightly better resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to technically limited resolution of the pH-gradient [28], a wide peak base was observed. Kang and Frey [37] compared different column packing of strong and weak ion-exchange adsorbents for chromatofocusing with regard to the linearity of the pH-gradient and resolution. It was reported that strong ion-exchange adsorbents could achieve the same or even slightly better resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…alternatively, the ProteomeLab PF2D platform (Beckman Coulter, USA) used for the quantitative comparisons and separation/fractionation of various biological and clinical samples, works in full automation combining chromatofocusing separation and hydrophobic fractionation 47 . During the first-dimension chromatofocusing of PF2D, proteins are first separated by their pI and then separated proteins with a pH gradient are collected using a fraction collector 48,49 . Subsequently, in the second dimension, the collected fractions from the first dimension are separated using reversed phase chromatography which works on the basis of hydrophobicity 49 .…”
Section: Automated Proteomic Analysis Using Proteomelab Pf2d Platformmentioning
confidence: 99%
“…Se utilizó el sistema de rotofor (Biorad, Richmond, Estados Unidos) para separar las proteínas por punto isoeléctrico (42). La fracción correspondiente a las proteínas asociadas con membrana se preparó así: 2,5 ml de muestra, 1 ml de anfolitos con rango de pH de 3 a 10, 3 ml de glicerol estéril y 11,5 ml de agua miliq estéril.…”
Section: Separación De Proteínas Por Punto Isoeléctricounclassified